2014
DOI: 10.1175/jamc-d-13-054.1
|View full text |Cite
|
Sign up to set email alerts
|

A Numeric Study of Regional Climate Change Induced by Urban Expansion in the Pearl River Delta, China

Abstract: The Pearl River Delta region has experienced rapid urbanization and economic development during the past 20 years. To investigate the impacts of urbanization on regional climate, the Advanced Research core of the Weather Research and Forecasting (ARW-WRF) model is used to conduct a pair of 1-yr simulations with two different representations of urbanization. Results show that the reduction in vegetated and irrigated cropland due to urban expansion significantly modifies the near-surface temperature, humidity, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(77 citation statements)
references
References 50 publications
6
70
1
Order By: Relevance
“…Compared with suburban regions, the increase in surface roughness induced by urban expansion can cause a 50% wind speed decrease in the YRDR, China. Similar results were also reported by Wang et al (2013), who used the same model in the same region and found that the building-induced friction leads to decreases in the SWS. The SWS over urban areas has decreased by approximately 1.2-1.5 m s −1 in the YRDR, and these values are similar to the results of Zha et al (2017a).…”
Section: The Advantages and Disadvantages Of Different Methodssupporting
confidence: 88%
“…Compared with suburban regions, the increase in surface roughness induced by urban expansion can cause a 50% wind speed decrease in the YRDR, China. Similar results were also reported by Wang et al (2013), who used the same model in the same region and found that the building-induced friction leads to decreases in the SWS. The SWS over urban areas has decreased by approximately 1.2-1.5 m s −1 in the YRDR, and these values are similar to the results of Zha et al (2017a).…”
Section: The Advantages and Disadvantages Of Different Methodssupporting
confidence: 88%
“…As reported in many previous studies, spatiotemporal urban land cover change is a serious concern both in megacities, such as Beijing [8,9], Shanghai [10][11][12], Hangzhou [13,14], and Guangzhou [15,16], and in developed coastal urban agglomerations, especially the three largest urban agglomerations, i.e., the Yangtze River Delta (YRD) [17,18], the Pearl River Delta (PRD) [19,20] and the Jing-Jin-Ji (JJJ) [21][22][23]. However, urban expansion in less developed cities and urban agglomerations has received little attention even though rapid urbanization has also occurred in these areas.…”
Section: Introductionmentioning
confidence: 89%
“…Numerous previous researches have shown that rapid urban expansion have occurred in the above three urban agglomerations over time [17,20,22,23], however, less for the MYRB urban agglomeration. To better understand the urban expansion in the MYRB urban agglomeration and the differences between the four national level urban agglomerations, a comparison of urban expansion rate among the four urban agglomerations was made.…”
Section: Urban Expansion In the Myrb Urban Agglomeration Compared Witmentioning
confidence: 99%
“…Additionally, a Single Layer Urban Canopy Model (SLUCM) coupled to the Noah land surface model (Noah/LSM) is adopted for a better modeling of the urban effects. Following the work of Q. and Wang et al (2014), the default values for urban canopy parameters in SLUCM are substituted by the typical values in South (Schell et al, 2001) China. As shown in Table 2, the values for building height, roof width, road width, urban fraction and surface albedo are modified for the cities in and outside PRD.…”
Section: Wrf/chem and Its Configurationmentioning
confidence: 99%